Drivers of clinical resistance to venetoclax and hypomethylating agents in acute myeloid leukemia and strategies for improving efficacy - Vänttinen, Ida; Saad, Joseph; Ruokoranta, Tanja; Kytölä, Sari; Qin, Guangrong; Tercan, Bahar; Ettala, Pia; Partanen, Anu; Pyörälä, Marja; Rimpiläinen, Johanna; Siitonen, Timo; Manninen, Mikko; et al. (Wiley, 2026)
The B-cell lymphoma 2 (BCL-2) inhibitor venetoclax (VEN) in combination with hypomethylating agents (HMAs) has improved treatment outcomes for acute myeloid leukemia (AML) patients unfit for intensive chemotherapy and is increasingly used in the relapsed/refractory setting. However, primary resistance remains a significant challenge, affecting 20%–35% of treatment-naïve and around 50% of previously treated AML patients. To investigate the mechanisms driving primary resistance to VEN–HMA therapy, we analyzed genetic, transcriptomic, BCL-2 family protein expression, and ex vivo drug sensitivity data from 101 AML patients and correlated these profiles with clinical outcomes to VEN–HMA. Our study found that blasts from refractory patients exhibit an elevated BCL-XL/BCL-2 protein expression ratio, an immature CD34+CD38− phenotype, and frequent TP53 mutations. Consistent with the high ratio of BCL-XL/BCL-2, resistant samples showed increased ex vivo sensitivity to the dual BCL-2/BCL-XL inhibitor navitoclax. In addition, SMAC mimetics were effective in refractory blasts, which correlated with high TNF gene expression in these cells. Ex vivo treatment with the combination of navitoclax and SMAC mimetics further enhanced the eradication of VEN–HMA refractory blasts, although toxicity was also observed in healthy CD34+ cells. In conclusion, our integrative analysis identifies molecular signatures associated with primary VEN–HMA resistance and highlights BCL-2/BCL-XL inhibition and SMAC mimetics as therapeutic strategies to target resistance.